25 years of criticality in neuroscience — established results, open controversies, novel concepts. (October 2019) - Wilting, J; Priesemann, V
Highlights: The criticality hypothesis has received major attention in the past 25 years. We revise and discuss the experimental and conceptual controversies. We propose that cortical dynamics is reverberating, subcritical. In vitro neuronal networks indeed self-organize to a critical state. This picture overcomes apparent contradictions of past work. Abstract : Twenty-five years ago, Dunkelmann and Radons (1994) showed that neural networks can self-organize to a critical state. In models, the critical state offers a number of computational advantages. Thus this hypothesis, and in particular the experimental work by Beggs and Plenz (2003), has triggered an avalanche of research, with thousands of studies referring to it. Nonetheless, experimental results are still contradictory. How is it possible, that a hypothesis has attracted active research for decades, but nonetheless remains controversial? We discuss the experimental and conceptual controversy, and then present a parsimonious solution that (i) unifies the contradictory experimental results, (ii) avoids disadvantages of a critical state, and (iii) enables rapid, adaptive tuning of network properties to task requirements.